Effect of Candesartan on Creatinine and Albuminuria in Geriatric Patients with Diabetic Nephropathy - Luh Gede Sri Yenny; Ni Wayan Rusni (Sean Institute, 2025)
Diabetes can cause various chronic complications, one of the most feared being diabetic nephropathy. Diabetic nephropathy is characterized by proteinuria and/or decreased glomerular filtration rate. Diabetic nephropathy is a major cause of chronic kidney disease, which can lead to end-stage renal disease requiring hemodialysis. Candesartan is an angiotensin receptor blocker antihypertensive drug. In addition to lowering blood pressure, candesartan is also thought to decrease renal vascular resistance, resulting in a decrease in microalbuminuria or proteinuria in patients with diabetes mellitus. Diabetic nephropathy increases with age, and geriatric patients have a lower response to therapy than adults. To determine the effect of candesartan on creatinine and albuminuria in geriatric patients with diabetic nephropathy. This was a cross-sectional study of 25 geriatric patients diagnosed with diabetic nephropathy who had been given 16 mg of candesartan as an antihypertensive at the Puri Raharja Hospital Denpasar outpatient clinic. Subjects who met the inclusion and exclusion criteria were recruited using consecutive sampling. The diabetic nephropathy subjects were evaluated for creatinine and proteinuria levels at the time of diagnosis and 3 months after receiving 16 mg of candesartan. All data were obtained from medical records. The study involved 25 patients consisting of 13 men (52%) and 12 women (485%). Subjects aged between 60-82 years with initial creatinine levels of 0.80-2.60 mg/dL, final creatinine levels of 1.395 ± 0.50 SD, initial positive proteinuria levels of 0-2, and final positive creatinine levels of 0-1. Based on the T-test, there was no significant difference between initial and final creatinine levels with a p value = 0.892 (95% CI -0.045-0.051). Based on the Wilcoxon test, there was a significant difference between proteinuria levels before and after candesartan administration with a p value p <0.05. This study did not find a significant decrease in creatinine after candesartan administration. However, candesartan significantly reduced proteinuria in geriatric patients with diabetic nephropathy.